2014
DOI: 10.1681/asn.2013010072
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-214 Antagonism Protects against Renal Fibrosis

Abstract: Renal tubulointerstitial fibrosis is the common end point of progressive renal disease. MicroRNA (miR)-214 and miR-21 are upregulated in models of renal injury, but the function of miR-214 in this setting and the effect of its manipulation remain unknown. We assessed the effect of inhibiting miR-214 in an animal model of renal fibrosis. In mice, genetic deletion of miR-214 significantly attenuated interstitial fibrosis induced by unilateral ureteral obstruction (UUO). Treatment of wild-type mice with an anti-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 48 publications
5
98
0
3
Order By: Relevance
“…Specific expression of miRNAs during kidney disease could serve as a potential diagnostic approach [see below and (336)]. Genetic deletion or treatment with antagonists in renal fibrosis showed that miR-21 (337), miR-214 (338), and miR-192 (339) are profibrotic whereas the miR-29 family (340), miR-200b (341), and miR-30e (342) are anti-fibrotic. Most of the miRs were suggested to target TGF-b signaling, collagen expression or metabolic pathways.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Specific expression of miRNAs during kidney disease could serve as a potential diagnostic approach [see below and (336)]. Genetic deletion or treatment with antagonists in renal fibrosis showed that miR-21 (337), miR-214 (338), and miR-192 (339) are profibrotic whereas the miR-29 family (340), miR-200b (341), and miR-30e (342) are anti-fibrotic. Most of the miRs were suggested to target TGF-b signaling, collagen expression or metabolic pathways.…”
Section: Epigeneticsmentioning
confidence: 99%
“…In renal cell carcinoma, miR-629, miR-192, miR-194 and miR-215 that are known to suppress tumor progression are significantly downregulated [117,118]. In diseased human kidney tissue, miR-214 was detected in the glomerulus and tubules and infiltrating immune cells and induced antifibrotic effects independent of Smad2 and Smad3 [119]. In a recent study, miRNA let-7 family members (let-7b/c/ d/g/i) were found to downregulate TGF-β-induced Smad, Col1A2 and Col4A1 expression, which is a key feature of diabetic nephropathy [120].…”
Section: Therapeutic Potential Of Smad Signaling In Renal Fibrosismentioning
confidence: 99%
“…Recent studies have reported differing roles of miR-214 in fibrosis: 3 in the kidney (Zarjou et al 2011;Denby et al 2011Denby et al , 2014, 1 in the liver (Chen et al 2014), and 1 in the heart (Aurora et al 2012). However, the pathophysiological roles of miR-214 in liver fibrosis remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%